High Purity Single Wall Carbon Nanotube by Oxygen-Containing Functional Group of Ferrocene-Derived Catalyst Precursor by Floating Catalyst Chemical Vapor Deposition - Moon, Sook Young; Jeon, Seung-Yeol; Lee, Sung-Hyun; Lee, Anna; Kim, Seung Min (MDPI, 2022)
Single wall carbon nanotubes (SWCNTs) were synthesized using oxygen-containing ferrocene derived catalysts. The mechanism of synthesizing carbon nanotubes was clarified by the catalyst's exothermic or endothermic decomposition processes. By monitoring the decomposition process of ferrocene-derived catalyst precursors with and without sulfur, we found that the types of oxygen function groups closely influence catalyst formation and nanotube growth. The ferrocene-derived catalyst precursors have a different oxygen containing groups, which are hydroxyl (-OH, ferrocenenemethanol) and carbonyl (C=O, acetylferrocene, and 1,1 ' -diacetylferrocene). The sulfur chemical state (S 2p) on synthesized catalyst particles using acetylferrocene and 1,1 ' -diacetylferrocene has more sulfate (SO42-) than others, and there also is a carbon state (C-S-C). The catalyst particle using ferrocenemethanol predominant formed metal-sulfur bonds (such as S2- and Sn2-). The hydroxyl group (-OH) of ferrocenemethanol enhanced the etching effect to remove amorphous carbon and prevented oxidation on the catalyst particle surfaces; however, the carbonyl group (C=O) of acetylferrocene reacted with the catalyst particles to cause partial oxidation and carbon dissociation on the surface of the catalyst particles. The partial oxidation and carbon contamination on catalyst particles controlled the activity of the catalyst. The DFT study revealed that the ferrocene-derived catalyst precursor was dissociated according to following process: the functional groups (such as CH3CO and COH) => first Cp ligands => second Cp ligands. The pyrolysis and release of Fe ions were delayed by the functional groups of ferrocene-derived precursors compared to ferrocene. The thermal-decomposition temperature of the catalyst precursor was high, the decomposition time was be delayed, affecting the formation of catalyst particles and thus making smaller catalyst particles. The size and composition of catalyst particles not only affect the nucleation of CNTs, but also affect physical properties. Therefore, the I-G/I-D ratio of the CNTs changed from 74 to 18 for acetylferrocene and ferrocene, respectively. The purity also increased from 79 to 90% using ferrocene-derived precursors.